The effect of sled towing or speed cord towing exercises on speed of riau pplm athletes - Agus Sulastio; Syahriadi; Ahmad Syukur Sitepu (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2019)
Based on observations in the field, the symptoms of sprinting are found when running speed, lowering feet and soles of the feet against soil contact is not optimal, step speed and step length are still slow and not maximal. The purpose of this study was to determine the effect of Sled Towing Exercise or Speed Cord Towing for the speed of PPLM Riau athlete. In this study, researchers took a population of 21 people. The sample in this study used a total sampling technique, where all populations were sampled. Data obtained from a 40-yard speed test category. Data were analyzed using the t-test. Based on the research that conducted on the sample by doing pre-test (initial test) by running in 40 yards, then proceed with treatment (Sled Towing or Speed Cord Towing) for 16 meetings. After that, it was post-tested (40-yard run), the results obtained from the pretest and posttest were analyzed by t-test. Hypothesis testing results show that the result of t-count is 7.364 with t-table 1.725 then H0 is rejected; Ha is accepted, at the alpha level (α) 0.05. It can be concluded that there is an effect of Sled Towing or Speed Cord Towing training on the speed of Riau PPLM athletes.